Public Debt in a Democratic Society - Buchanan, James M.; Wagner, Richard E. (Washington, American Enterprise Institute for Public Policy Research, 1967)
Early in the discussion, some clarification are made at the widespread confusion between public debt and money. The second major part discusses the management of the national debt.
Bibliography: p. 67.
osc 21/6/17
Loans
Keywords: Debts, Public